Molecular Evolution and Expansion of the KUP Family in the Allopolyploid Cotton Species Gossypium hirsutum and Gossypium barbadense - Fan, Kai; Mao, Zhijun; Zheng, Jiaxin; Chen, Yunrui; Li, Zhaowei; Lin, Weiwei; Zhang, Yongqiang; Huang, Jinwen; Lin, Wenxiong (Frontiers in Plant Science, 2020)
The comprehensive analysis of gene family evolution will elucidate the origin and evolution of gene families. The K+ uptake (KUP) gene family plays important roles in K+ uptake and transport, plant growth and development, and abiotic stress responses. However, the current understanding of the KUP family in cotton is limited. In this study, 51 and 53 KUPs were identified in Gossypium barbadense and Gossypium hirsutum, respectively. These KUPs were divided into five KUP subfamilies, with subfamily 2 containing three groups. Different subfamilies had different member numbers, conserved motifs, gene structures, regulatory elements, and gene expansion and loss rates. A paleohexaploidization event caused the expansion of GhKUP and GbKUP in cotton, and duplication events in G. hirsutum and G. barbadense have happened in a common ancestor of Gossypium. Meanwhile, the KUP members of the two allopolyploid subgenomes of G. hirsutum and G. barbadense exhibited unequal gene proportions, gene structural diversity, uneven chromosomal distributions, asymmetric expansion rates, and biased gene loss rates. In addition, the KUP families of G. hirsutum and G. barbadense displayed evolutionary conservation and divergence. Taken together, these results illustrated the molecular evolution and expansion of the KUP family in allopolyploid cotton species.